Polyester material as well as preparation method and application thereof

By introducing specific structural units A and structural units B into the polyester material, the problem of the glass transition temperature dropping in the prior art when the melting point is reduced, the possibility of nozzle blockage is reduced during the preparation of non-woven fabrics by spinning or meltblowning is realized, and the application efficiency of the material is improved.

CN119570002AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311138742.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

The prior art reduces the melting point of the polyester material, while reducing the glass transition temperature, resulting in a tendency to clog the nozzle during the preparation of the nonwoven fabric by spinning or meltblowing.

Method used

By introducing specific structural units A and structural units B into the polyester material, and reacting under esterification and polycondensation reaction conditions, a polyester material can be prepared that can avoid or increase the glass transition temperature while reducing the melting point.

Benefits of technology

The possibility of nozzle blockage is reduced during the preparation of non-woven fabrics by spinning or meltblowning is achieved, the application efficiency of materials is improved, and the strength and breathability of spinning or non-woven fabrics are basically no impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570002A_ABST
    Figure CN119570002A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer material, and discloses a polyester material as well as a preparation method and application thereof. The polyester material is a polymer containing a structural unit A as shown in a formula (I) and a structural unit B as shown in a formula (II), wherein R1, R2 and R3 are respectively and independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are respectively and independently hydrogen or C1-C6 alkyl, and n is a positive integer from 3 to 20. The preparation method comprises the following steps: (1) under an esterification reaction condition, mixing a dihydric alcohol monomer, a dibasic acid monomer, a modified monomer and a catalyst, and carrying out a first-stage reaction to obtain a prepolymer; the modified monomer comprises dihydric alcohol with a structure as shown in a formula (I) and dibasic acid with a structure as shown in a formula (II); and (2) carrying out a second-stage reaction on the prepolymer under a polycondensation reaction condition. According to the polyester material, the melting point can be effectively reduced, and meanwhile, the glass-transition temperature is prevented from being reduced. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyester material, in particular to a polyester material and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a semi-crystalline thermoplastic polyester and an engineering plastic with good comprehensive properties. PBT has good processing properties and a faster crystallization rate than PET resin. PBT products have excellent electrical conductivity and mechanical properties and are widely used in electronic products, daily necessities, automobiles and other fields.

[0003] With the continuous expansion of the application scope of PBT, PBT non-woven fabrics are widely used in various filter materials, such as air filter materials, vehicle oil filter materials and water filter materials. The use effect of PBT non-woven fabrics is significantly better than that of PET non-woven fabrics. Conventional PBT cannot be used to produce non-woven PBT materials due to its high melting point. PBT with a lower melting point must be used, and the melting point must be lower than 170°C. The most suitable melting point is 150-170°C. Due to the particularity of the production equipment, the PBT used to produce non-woven fabrics not only has a low melting point, but also requires this low-melting-point PBT to have a relatively high glass transition temperature, because PBT with a low glass transition temperature is easy to clog the nozzle of the spray gun. At present, ordinary low-melting-point PBT on the market needs to be stopped regularly to clean the nozzle of the spray gun.

[0004] In the prior art, other comonomers are added during the production of PBT. The addition of other comonomers can destroy the regularity of the PBT macromolecular chain, reduce its crystallization performance, and achieve the purpose of lowering the melting point; however, it will also cause the glass transition temperature of PBT to drop, and it is lower than the glass transition temperature of conventional PBT. For example, CN102344554A discloses a method for preparing a low-melting-point PBT copolyester, wherein phthalic acid includes terephthalic acid and isophthalic acid, but the PBT prepared by this method will reduce the crystallization performance and melting point of PBT, and will also cause its glass transition temperature to drop.

[0005] The current method for preparing low-melting point polyester is to add some monomers for copolymerization modification. These monomers mainly include isophthalic acid, adipic acid, ethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 2,2-methyl-1,3-propanediol, etc. The addition of these monomers will reduce the crystallization properties and melting point of PBT, and will cause its glass transition temperature to decrease. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem in the prior art that the glass transition temperature of polyester materials will decrease while the melting point is reduced, and to provide a polyester material and a preparation method and application thereof.

[0007] During the research process, the inventors of the present invention unexpectedly discovered that the polymer containing the structural unit A represented by formula (I) and the structural unit B represented by formula (II) can effectively reduce the melting point of the polyester material while avoiding the decrease of its glass transition temperature, and can even effectively reduce the melting point of the polyester material while increasing its glass transition temperature, thereby reducing the possibility of nozzle clogging during the spinning process or the process of preparing non-woven fabrics by melt blowing, facilitating subsequent applications in spinning or preparing non-woven fabrics by melt blowing.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a polyester material, which is a polymer containing a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0009]

[0010]

[0011] Wherein, R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20.

[0012] A second aspect of the present invention provides a method for preparing a polyester material, comprising the following steps:

[0013] (1) under esterification reaction conditions, diol monomer, dibasic acid monomer, modified monomer and catalyst are mixed to carry out a first stage reaction to obtain a prepolymer;

[0014] The modified monomer includes a diol having a structure represented by formula (I) and a dibasic acid having a structure represented by formula (II);

[0015]

[0016] wherein R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20;

[0017] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0018] The third aspect of the present invention provides the use of the aforementioned polyester material or the polyester material prepared by the aforementioned preparation method in spinning.

[0019] The polyester material provided by the present invention is a polymer containing a structural unit A represented by formula (I) and a structural unit B represented by formula (II), which can effectively reduce the melting point of the polyester material while avoiding a decrease in the glass transition temperature, and can even effectively reduce the melting point of the polyester material while increasing its glass transition temperature, thereby reducing the possibility of nozzle clogging during the spinning process or the process of preparing non-woven fabrics by the melt-blowing method, and facilitating subsequent applications in spinning or preparing non-woven fabrics by the melt-blowing method.

[0020] Taking PBT material as an example, when PBT contains the above-mentioned structural unit A and structural unit B, the melting point of PBT can be as low as 150°C. Compared with conventional PBT, its glass transition temperature is also improved, which can reduce the possibility of nozzle clogging during the spinning process or the melt-blowing process for preparing non-woven fabrics, and facilitate subsequent applications in spinning or the melt-blowing process for preparing non-woven fabrics. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] As mentioned above, the first aspect of the present invention provides a polyester material, which is a polymer containing a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0023]

[0024] Wherein, R1, R2 and R3 are each independently hydrogen, hydroxyl, or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20.

[0025] According to the present invention, R1, R2 and R3 can be independently hydrogen, hydroxyl, linear C1-C6 alkyl, branched C1-C6 alkyl or C1-C6 cycloalkyl, for example, hydrogen, hydroxyl, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl and cyclobutyl, etc. R4 can be hydrogen, linear C1-C6 alkyl, branched C1-C6 alkyl or C1-C6 cycloalkyl. For example, it may be hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl, cyclobutyl, etc. R6, R7, R8 and R9 are each independently hydrogen, a linear C1-C6 alkyl, a branched C1-C6 alkyl or a C1-C6 cycloalkyl, for example, it may be hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl, cyclobutyl, etc.

[0026] The structural unit A and structural unit B can be obtained by performing infrared and nuclear magnetic resonance detection and analysis on the polyester material.

[0027] The polyester material provided by the present invention is a polymer containing the structural unit A represented by the above formula (I) and the structural unit B represented by the above formula (II). Under the action of the above two structural units, the melting point of the polyester material can be effectively reduced while avoiding the decrease of the glass transition temperature, and can even effectively reduce the melting point of the polyester material while increasing its glass transition temperature, thereby reducing the possibility of nozzle clogging during the spinning process or the process of preparing non-woven fabrics by melt-blowing, and facilitating subsequent applications in spinning or preparing non-woven fabrics by melt-blowing.

[0028] Preferably, R1 is hydrogen or hydroxyl, R2 and R3 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-15. Limiting R1, R2 and R3 within the above range can further reduce the melting point of the polyester. In order to further reduce the melting point of the polyester, it is further preferred that R2, R3, R4, R6, R7, R8 and R9 are each independently hydrogen or methyl, and n is a positive integer of 3-10. More preferably, R2, R3, R4, R6, R7, R8 and R9 are hydrogen.

[0029] Preferably, the polymer further contains a structural unit C represented by formula (III) and a structural unit D represented by formula (IV);

[0030]

[0031] Among them, R 10 , R 11 , R 12 and R 13 Each is independently C1-C6 alkyl or hydrogen, and R5 is C2-C10 alkylene. 10 , R 11 , R 12 and R 13 Each of them can be independently hydrogen, a straight-chain alkyl, a branched alkyl or a cycloalkyl, specifically hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl and cyclobutyl, etc.; R5 can be a C2-C10 straight-chain alkylene or a C2-C10 branched alkylene. Studies have shown that the polymer provided above contains both structural unit C and structural unit D, which can further reduce the melting point of the polyester material. In view of being able to further reduce the melting point of the polyester material, it is further preferred that the R 10 , R 11 , R 12 and R 13 Each is independently methyl or hydrogen, and R5 is C2-C6 alkylene. 10 , R 11 , R 12 and R 13 is hydrogen, and said R5 is C2-C4 alkylene.

[0032] Preferably, in the polymer, the weight percentage of the structural unit A is 1-8.5%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 8.5%, or any value between these values; the molar amount of the structural unit B accounts for 10-75% of the total molar amount of the structural unit B and the structural unit C, specifically 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, or any value between these values. Studies have found that controlling the content of the structural unit A and the structural unit B within the above range can further improve the interaction effect of the structural unit A and the structural unit B, thereby further reducing the melting point of the polyester material while further increasing the glass transition temperature of the polyester material.

[0033] Specifically, the weight percentage of the structural unit A and the molar percentage of the structural unit B can be calculated by nuclear magnetic resonance or gas chromatography.

[0034] Preferably, the melting point of the polyester material is less than or equal to 215°C, and the glass transition temperature is 34°C, which can reduce the possibility of nozzle clogging during melting, and facilitate the subsequent application in the preparation of non-woven fabrics by melt-blowing. Further preferably, the melting point of the polyester material is less than or equal to 190°C, and the glass transition temperature is 36-80°C.

[0035] According to the present invention, the melting point and the glass transition temperature are measured by a differential scanning calorimeter DSC8500 of PE Company. Wherein, the process of calculating the glass transition temperature by differential scanning calorimetry (DSC) test includes: under nitrogen protection, using DSC thermal analysis to increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, keep it for 5 minutes, then cool it down to 25°C at a rate of 400°C / min, then increase it from 25°C to 290°C at a heating rate of 10°C / min, keep it for 5 minutes, and finally cool it down to 100°C at a rate of 10°C / min, and calculate the glass transition temperature Tg and the melting point Tm according to the second heating curve.

[0036] Preferably, the polyester material has a terminal carboxyl group of 20-38 mol / t and an intrinsic viscosity of 0.7-1 dL / g, which further facilitates subsequent application in the preparation of non-woven fabrics by melt-blowing.

[0037] According to the present invention, the intrinsic viscosity is tested and characterized according to 5.1 of "Test Method for Fiber-Grade Polyester Chips GB / T14190-2017", and the terminal carboxyl group is tested and characterized according to 5.4 of "Test Method for Fiber-Grade Polyester Chips GB / T14190-2017".

[0038] A second aspect of the present invention provides a method for preparing a polyester material, comprising the following steps:

[0039] (1) under esterification reaction conditions, diol monomer, dibasic acid monomer, modified monomer and catalyst are mixed to carry out a first stage reaction to obtain a prepolymer;

[0040] The modified monomer includes a diol having a structure represented by formula (I) and a dibasic acid having a structure represented by formula (II);

[0041]

[0042]

[0043] wherein R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20;

[0044] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0045] Specifically, the structure of the diol containing the structure shown in formula (I) is as follows:

[0046] Wherein, R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, and n is a positive integer of 3-20.

[0047] The dibasic acid having the structure shown in formula (II) is as follows:

[0048] Wherein, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl.

[0049] According to the present invention, R1, R2 and R3 can be independently hydrogen, hydroxyl, linear C1-C6 alkyl, branched C1-C6 alkyl or C1-C6 cycloalkyl, for example, hydrogen, hydroxyl, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl and cyclobutyl, etc. R4 can be hydrogen, linear C1-C6 alkyl, branched C1-C6 alkyl or C1-C6 cycloalkyl. For example, it may be hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl, cyclobutyl, etc. R6, R7, R8 and R9 are each independently hydrogen, a linear C1-C6 alkyl, a branched C1-C6 alkyl or a C1-C6 cycloalkyl, for example, it may be hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopropyl, cyclobutyl, etc. The end condition of the first stage reaction can be determined by the experimenter according to the actual situation, preferably, it can be determined according to the amount of water in the product. In a specific embodiment of the present invention, the end condition of the first stage reaction is: when the amount of water collected reaches 90% of the theoretical value, the esterification reaction ends.

[0050] The end condition of the second stage reaction can also be determined by the experimenter according to the actual situation, preferably, it can be determined according to the viscosity of the reaction system or according to whether the stirring current reaches the rated value. In a specific embodiment of the present invention, the end condition of the second stage reaction is: the stirring current reaches the rated value.

[0051] During the research process, the inventors found that the polyester material prepared by the above preparation method can effectively reduce the melting point of the polyester material while avoiding the decrease of the glass transition temperature, thereby reducing the possibility of nozzle clogging during the spinning process or the process of preparing non-woven fabrics by melt blowing, facilitating subsequent applications in spinning or preparing non-woven fabrics by melt blowing.

[0052] Preferably, R1 is hydrogen, hydroxyl or C1-C6 hydroxyalkyl, R2 and R3 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-15. Within the above range, the melting point of the polyester material can be further reduced. Considering that the melting point of the polyester material can be further reduced, preferably, R1 is hydrogen or hydroxyl, R2, R3, R4, R6, R7, R8 and R9 are each independently hydrogen or methyl, and n is a positive integer of 3-10. Further preferably, R2, R3, R4, R6, R7, R8 and R9 are hydrogen.

[0053] Preferably, the dibasic acid monomer is a dibasic acid having a structure represented by formula (III), and the diol monomer is a diol having a structure represented by formula (IV);

[0054]

[0055] Among them, R 10 , R 11 , R 12 and R 13 Each independently represents a C1-C6 alkyl group or hydrogen, and R5 represents a C2-C10 alkylene group. Studies have shown that when the comonomer includes a dibasic acid having a structure represented by formula (III) and a diol having a structure represented by formula (IV), the melting point of the polyester material can be further reduced. In order to further reduce the melting point of the polyester material, it is further preferred that the R 10 , R 11 , R 12 and R 13 Each is independently C1-C4 alkyl or hydrogen, and R5 is C2-C6 alkylene. Further preferably, R 10 , R 11 , R 12 and R 13 Each independently is methyl or hydrogen. More preferably, the R10 , R 11 , R 12 and R 13 is hydrogen, and R5 is C2-C4 alkylene.

[0056] Specifically, the structural formulas of the dibasic acid having the structure represented by formula (III) and the diol having the structure represented by formula (IV) are as follows:

[0057] HO-R5-OH, where R 10 , R 11 , R 12 and R 13 Each is independently C1-C6 alkyl or hydrogen, and R5 is C2-C10 alkylene.

[0058] Preferably, in step (1), in step (1), the weight ratio of the diol containing the structure shown in formula (I) to the dibasic acid containing the structural unit shown in formula (II) is 1:1-80, preferably 1:1-20, and more preferably 1:5-10. Further preferably, in step (1), relative to 100g of dibasic acid monomer, the addition amount of the diol monomer is 80-260g, the addition amount of the modified monomer is 10-280g, and the addition amount of the catalyst is 0.03-0.3g; the polyester material prepared under the above conditions has a lower melting point. Preferably, the catalyst is a titanate catalyst and / or an antimony-containing catalyst, specifically any catalyst containing a titanate structure or a catalyst containing antimony. Further preferably, the titanate catalyst is tetrabutyl titanate and / or tetraethyl titanate, and the antimony-containing catalyst is selected from at least one of ethylene glycol antimony, antimony acetate and antimony trioxide.

[0059] Preferably, in step (1), the esterification reaction conditions at least include: isolation of oxygen, a temperature of 180°C-260°C, specifically 180°C, 200°C, 220°C, 240°C, 260°C, or any value between the aforementioned values. Under the above conditions, the diol monomer, the dibasic acid monomer and the modified monomer have a better esterification effect, which can further reduce the melting point of the subsequently obtained polyester. Isolation of oxygen is usually achieved by filling the reaction system with an inert gas such as nitrogen or helium. The first stage reaction is carried out under stirring, and the stirring rate can be determined by the experimenter according to actual conditions.

[0060] Preferably, in step (2), the polycondensation reaction conditions at least include: a temperature of 245-290°C, specifically 245°C, 255°C, 265°C, 275°C, 285°C, 290°C, or any value in between; and an absolute vacuum degree of less than 100 Pa. Under the above conditions, the ester monomer obtained by the esterification has a better polycondensation effect, which can further reduce the melting point of the subsequently obtained polyester.

[0061] According to the present invention, before reaching the polycondensation reaction conditions, the cooling rate is 0.6-1.5°C / min.

[0062] The third aspect of the present invention provides the use of the above polyester material or the polyester material prepared by the above preparation method in spinning.

[0063] Preferably, the third aspect of the present invention provides the use of the above polyester material or the polyester material prepared by the above preparation method in the preparation of non-woven fabrics by meltblowing.

[0064] The polyester material has a relatively low melting point and can also increase its glass transition temperature, and is well applied in spinning or preparing non-woven fabrics, will not clog the nozzle, and reduces the difficulty of preparation.

[0065] According to a particularly preferred embodiment of the present invention, the method for preparing the aliphatic-aromatic polyester comprises the following steps:

[0066] (1) A diol having a structure represented by formula (I), a dibasic acid having a structure represented by formula (II), a dibasic acid having a structure represented by formula (III), a diol having a structure represented by formula (IV), and a catalyst are stirred and slurried, and after nitrogen replacement three times, the mixture is heated to 180-260° C. and esterified under normal pressure. When the esterification water output reaches 90% of the theoretical amount, the esterification is terminated;

[0067]

[0068]

[0069] wherein R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4, R6, R7, R8, R9, R 10 , R 11 , R 12 and R 13Each is independently a C1-C6 alkyl or hydrogen, R5 is a C2-C10 alkylene, and n is 3-20; the weight ratio of the diol containing the structure represented by formula (I) to the dibasic acid containing the structural unit represented by formula (II) is 1:1-80, the added amount of the diol containing the structure represented by formula (IV) is 80-260g relative to 100g of the dibasic acid containing the structure represented by formula (III), the total added amount of the diol containing the structure represented by formula (I) and the dibasic acid containing the structural unit represented by formula (II) is 10-280g, and the added amount of the catalyst is 0.03-0.3g;

[0070] (2) The esterification product is heated under reduced pressure for 45 minutes to a temperature of 245-290° C. and a vacuum degree of less than 100 Pa, entering a high vacuum polycondensation stage. When the stirring current reaches a rated value, the material is discharged to obtain a polyester material.

[0071] The polyester material prepared by the above method has a lower melting point and can also increase its glass transition temperature, and has good application in spinning or preparing non-woven fabrics, will not block the nozzle, and reduces the difficulty of preparation. In addition, it provides a new method for preparing low-melting-point polyester.

[0072] The present invention will be described in detail below through examples.

[0073] In the following embodiments, the detection methods of various parameters and performances are as follows:

[0074] (1) The glass transition temperature and melting point were calculated by differential scanning calorimetry (DSC). The specific process was as follows: under nitrogen protection, DSC thermal analysis was used to increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 min, then cool to 25°C at a rate of 400°C / min, then increase the temperature from 25°C to 290°C at a heating rate of 10°C / min, hold for 5 min, and finally cool to 100°C at a rate of 10°C / min. The glass transition temperature Tg and melting point Tm were calculated based on the second heating curve.

[0075] (2) The intrinsic viscosity is tested according to 5.1 of GB / T14190-2017 Test Method for Fiber-Grade Polyester Chips.

[0076] (3) The terminal carboxyl group is tested according to the method of GB / T14190-2017.

[0077] (4) Air permeability is tested according to GB / T5453 method.

[0078] (5) The breaking strength is tested according to the method of GB / T3923.1.

[0079] (6) The original air resistance is tested according to the GOSTR ISO11092:2012 method.

[0080] (7) The weight percentage of structural unit A is calculated by NMR measurement.

[0081] (8) The molar percentage of structural unit B is calculated by gas chromatography measurement.

[0082] In the following examples, the chemical formula of the linear condensate of phenol and formaldehyde (A) is shown in formula (V),

[0083]

[0084] The chemical formula of the linear condensate of phenol and formaldehyde (C) is shown in formula (VI),

[0085]

[0086] The chemical formula of the linear condensate of phenol and formaldehyde (D) is shown in formula (VII),

[0087]

[0088] The chemical formula of the linear condensate of resorcinol and formaldehyde (B) is shown in formula (VIII),

[0089]

[0090] The chemical formula of the linear condensate of resorcinol and formaldehyde (E) is shown in formula (IX),

[0091]

[0092] The above linear condensates were all purchased from commercial suppliers, and the remaining raw materials were all chemically pure.

[0093] Example 1

[0094] In a 2L reactor, 315g of terephthalic acid, 35g of isophthalic acid, 4.7g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0095] Example 2

[0096] In a 2L reactor, 280g of terephthalic acid, 70g of isophthalic acid, 10g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0097] Example 3

[0098] In a 2L reactor, 250g of terephthalic acid, 100g of isophthalic acid, 14.5g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0099] Example 4

[0100] In a 2L reactor, add 210g of terephthalic acid, 140g of isophthalic acid, 20g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate and mix evenly. After nitrogen replacement three times, heat to 210°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0101] Example 5

[0102] In a 2L reactor, 175g of terephthalic acid, 175g of isophthalic acid, 24g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0103] Example 6

[0104] In a 2L reactor, 140g of terephthalic acid, 210g of isophthalic acid, 28g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0105] Example 7

[0106] In a 20L reactor, 2kg of terephthalic acid, 3kg of isophthalic acid, 3kg of ethylene glycol, 47g of linear condensate of resorcinol and formaldehyde (B) and 3g of ethylene glycol antimony were added and esterification was carried out at a temperature of 230°C and a pressure (gauge pressure) of 2.5MPa. When the water output reached 90% of the theoretical amount, the esterification was terminated, the pressure was vented to normal pressure, and stirring was continued for 10min. The temperature was gradually increased to enter the low vacuum stage. After the heating time was 45min, polycondensation was carried out at a temperature of 280°C and a vacuum degree of <100Pa. The material was discharged when the stirring power reached the rated value to obtain a polyester material.

[0107] Example 8

[0108] In a 20L reactor, 2.5kg of terephthalic acid (PAT), 2.5kg of isophthalic acid, 3kg of ethylene glycol, 35g of linear condensate of resorcinol and formaldehyde (E), and 3g of ethylene glycol antimony were added and esterification was carried out at a temperature of 220°C and a pressure (gauge pressure) of 2.6MPa. When the water output reached 90% of the theoretical amount, the esterification was terminated, the pressure was vented to normal pressure, and stirring was continued for 10min. The temperature was gradually increased to enter the low vacuum stage. After the heating time was 45min, polycondensation was carried out at a temperature of 280°C and a vacuum degree of <100Pa. The material was discharged when the stirring power reached the rated value to obtain a polyester material.

[0109] Example 9

[0110] In a 20L polymerization kettle, 4.38kg of terephthalic acid, 0.62kg of isophthalic acid, 4.12kg of 1,3-propylene glycol, 558g of a linear condensate of phenol and formaldehyde (A), 3.32g of antimony glycol and 2.12g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.18MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, and the vacuum pressure was less than 100Pa), the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain a polyester material.

[0111] Example 10

[0112] In a 2L reactor, 100g of terephthalic acid, 250g of isophthalic acid, 28g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0113] Embodiment 11

[0114] In a 2L reactor, add 210g of terephthalic acid, 140g of isophthalic acid, 20g of phenol and formaldehyde linear condensate (C), 360g of 1,4-butanediol and 0.17g of catalyst tetraethyl titanate and mix evenly. After nitrogen replacement three times, heat to 180°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 245°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0115] Example 12

[0116] In a 2L reactor, 175g of terephthalic acid, 175g of isophthalic acid, 24g of phenol and formaldehyde linear condensate (D), 360g of 1,4-butanediol and 0.35g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 230°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 265°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0117] Comparative Example 1

[0118] In a 2L reactor, add 350g of terephthalic acid, 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate and mix evenly. After nitrogen replacement three times, heat to 210°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0119] Comparative Example 2

[0120] In a 2L reactor, add 315g of terephthalic acid, 35g of isophthalic acid, 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate and mix evenly. After nitrogen replacement three times, heat to 210°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0121] Comparative Example 3

[0122] PBT was prepared according to the method described in Comparative Example 2, and the obtained PBT was mixed with 4.7 g of a linear condensate of phenol and formaldehyde (A) to obtain a mixed polyester material.

[0123] Comparative Example 4

[0124] In a 2L reactor, 350g of terephthalic acid, 20g of phenol and formaldehyde linear condensate (A), 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate were added and mixed evenly. After nitrogen replacement three times, the temperature was raised to 210°C. When the esterification water reached 90% of the theoretical amount, the temperature was gradually raised and transferred to the low vacuum stage. The heating time was 45min, and then the reaction was carried out at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0125] Comparative Example 5

[0126] In a 2L reactor, add 210g of terephthalic acid, 140g of isophthalic acid, 360g of 1,4-butanediol and 0.3g of catalyst tetraethyl titanate and mix evenly. After nitrogen replacement three times, heat to 210°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0127] Comparative Example 6

[0128] In a 2L reactor, add 175g of terephthalic acid, 175g of isophthalic acid, 360g of 1,4-butanediol and 0.3g of catalyst tetrabutyl titanate and mix evenly. After nitrogen replacement three times, heat to 210°C. When the esterification water reaches 90% of the theoretical amount, gradually increase the temperature and switch to the low vacuum stage. After the heating time is 45min, react at a temperature of 255°C and a vacuum degree of ﹤100Pa. When the stirring power reaches the rated value, discharge the material to obtain a polyester material.

[0129] Comparative Example 7

[0130] 2.5 kg of terephthalic acid (PAT), 2.5 kg of isophthalic acid, 3 kg of ethylene glycol and 3 g of ethylene glycol antimony were added to a 20 L reactor, and esterification was carried out at a temperature of 220 ° C and a pressure (gauge pressure) of 2.6 MPa. When the water output reached 90% of the theoretical value, the esterification was terminated, the pressure was vented to normal pressure, and stirring was continued for 10 minutes. The temperature was gradually increased to enter the low vacuum stage. After the low vacuum time was about 45 minutes, the high vacuum polycondensation stage (pressure <100 Pa) was entered, and polycondensation was carried out at a temperature of 280 ° C. When the stirring power reached the rated value, the material was discharged to obtain a polyester material.

[0131] Comparative Example 8

[0132] In a 20L polymerization kettle, 5kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 558g of a linear condensate of phenol and formaldehyde (A), 3.32g of antimony glycol and 2.12g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added into a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.18MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, and the vacuum pressure was less than 100Pa), the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain a polyester material.

[0133] Test Case

[0134] The polyesters prepared in the above examples and comparative examples were tested for physical and chemical properties, and the obtained data are shown in Table 1:

[0135] Table 1

[0136]

[0137]

[0138] It can be seen from the results in Table 1 that, compared with the comparative example, the polyester provided in the embodiment reduces the melting point of the material and improves the glass transition temperature through the interaction between the two structural units, indicating that the technical solution within the protection scope of the present invention can reduce the melting point while increasing the glass transition temperature, thereby reducing the possibility of nozzle clogging during the spinning process or the process of preparing non-woven fabrics by melt-blowing, and facilitating subsequent applications in spinning or preparing non-woven fabrics by melt-blowing.

[0139] Test Example 2

[0140] After the polyester material is dried (to make its moisture content less than 100ppm), it is melt-plasticized and spun by a screw, and the diameter of the spinneret hole is 0.25m to prepare a non-woven fabric. The properties of the obtained non-woven fabric and the nozzle conditions during the preparation process are shown in Table 2:

[0141] Table 2

[0142]

[0143] The above description shows that when the polyester provided by the present invention is used to prepare non-woven fabrics, the nozzle cleaning cycle is significantly improved, indicating that the polyester provided by the present invention can reduce the possibility of nozzle clogging, and the preparation of non-woven fabrics by using the polyester has basically no effect on its strength and air permeability.

[0144] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyester material, characterized in that: The polyester material is a polymer containing a structural unit A represented by formula (I) and a structural unit B represented by formula (II); Wherein, R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20.

2. The polyester material according to claim 1, characterized in that: R1 is hydrogen or hydroxyl, R2 and R3 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-15; Preferably, R2, R3, R4, R6, R7, R8 and R9 are each independently hydrogen or methyl, and n is a positive integer of 3-10; Preferably, R2, R3, R4, R6, R7, R8 and R9 are hydrogen.

3. The polyester material according to claim 1 or 2, characterized in that: The polymer further comprises a structural unit C represented by formula (III) and a structural unit D represented by formula (IV); Among them, R 10 , R 11 , R 12 and R 13 Each is independently C1-C6 alkyl or hydrogen, and R5 is C2-C10 alkylene; Preferably, the R 10 , R 11 , R 12 and R 13 Each is independently methyl or hydrogen, and R5 is a C2-C6 alkylene group; Preferably, the R 10 , R 11 , R 12 and R 13 is hydrogen, and R5 is C2-C4 alkylene.

4. The polyester material according to claim 3, characterized in that: In the polymer, the weight percentage of the structural unit A is 1-8.5%, and the molar amount of the structural unit B accounts for 10-75% of the total molar amount of the structural unit B and the structural unit C.

5. The polyester material according to claim 1 or 2, characterized in that: The melting point of the polyester material is less than or equal to 215°C, and the glass transition temperature is greater than 34°C; Preferably, the polyester material has a melting point less than or equal to 190°C and a glass transition temperature of 36-80°C.

6. A method for preparing a polyester material, characterized in that: The steps include: (1) under esterification reaction conditions, diol monomer, dibasic acid monomer, modified monomer and catalyst are mixed to carry out a first stage reaction to obtain a prepolymer; The modified monomer includes a diol having a structure represented by formula (I) and a dibasic acid having a structure represented by formula (II); wherein R1, R2 and R3 are each independently hydrogen, hydroxyl or C1-C6 alkyl, R4 is C1-C6 alkyl or hydrogen, R6, R7, R8 and R9 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-20; (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

7. The preparation method according to claim 6, characterized in that: In step (1), the weight ratio of the diol having the structure represented by formula (I) to the dibasic acid having the structure represented by formula (II) is 1:1-80, preferably 1:1-20, and more preferably 1:5-10; Preferably, R1 is hydrogen or hydroxyl, R2 and R3 are each independently hydrogen or C1-C6 alkyl, and n is a positive integer of 3-15; Preferably, R2, R3, R4, R6, R7, R8 and R9 are each independently hydrogen or methyl, and n is a positive integer of 3-10; Preferably, R2, R3, R4, R6, R7, R8 and R9 are hydrogen.

8. The preparation method according to claim 6 or 7, characterized in that: The dibasic acid monomer is a dibasic acid having a structure represented by formula (III), and the diol monomer is a diol having a structure represented by formula (IV); Among them, R 10 , R 11 , R 12 and R 13 Each is independently C1-C6 alkyl or hydrogen, and R5 is C2-C10 alkylene; Preferably, the R 10 , R 11 , R 12 and R 13 Each is independently methyl or hydrogen, and R5 is C2-C6 alkylene; Preferably, R1, R2, R3, R4, R6, R7, R8, R9, R 10 , R 11 , R 12 and R 13 is hydrogen, and said R5 is C2-C4 alkylene.

9. The preparation method according to claim 6 or 7, characterized in that: In step (1), relative to 100 g of the dibasic acid monomer, the amount of the diol monomer added is 80-260 g, the amount of the modified monomer added is 10-280 g, and the amount of the catalyst added is 0.03-0.3 g; Preferably, the catalyst is a titanate catalyst and / or an antimony-containing catalyst; Preferably, the titanate catalyst is tetrabutyl titanate and / or tetraethyl titanate, and the antimony-containing catalyst is selected from at least one of ethylene glycol antimony, antimony acetate and antimony trioxide.

10. The preparation method according to claim 6 or 7, characterized in that: In step (1), the esterification reaction conditions include at least: a temperature of 180°C-260°C; In step (2), the polycondensation reaction conditions at least include: a temperature of 245-290° C. and an absolute vacuum degree of less than 100 Pa.

11. Use of the polyester material according to any one of claims 1 to 5 or the polyester material prepared by the preparation method according to any one of claims 6 to 10 in spinning.

Citation Information

Patent Citations

  • Preparation method for low melting point PBT copolyester

    CN102344554A

  • Preparation method of phenolic resin modified water-based saturated polyester resin

    CN103865050A

  • Waterborne impregnating insulation varnish capable of being quickly cured at low temperature and preparation method thereof

    CN104194581A

  • Toughening modified phenolic resin and preparation method thereof

    CN104327229A

  • Modified polyester paint with good adhesion and preparation method thereof

    CN111732877A